Isolation and characterization of Acetobacter aceti from rotten papaya - Kowser, J; Aziz, MG; Uddin, MB (Journal of the Bangladesh Agricultural University, 2016)
The present study was concerned with the isolation and characterization of Acetobacter aceti from rotten papaya for vinegar production. The samples were inoculated in sterilized GYC standard media and then incubated at 30°C for 48 hours. Successive subculture was performed to screen out the strains. In Grams staining, the morphology of the isolated bacteria exhibited pink, small rod shaped single, pair and chain in arrangement, in the hanging drops technique, all the isolates revealed motile. Biochemical tests were performed by fermentation of five basic sugars by producing both acid and gas bubbles in Durham tube. All of the isolates were Indole, Voges-Proskauer (VP) and Oxidase negative, Methyl Red (MR) and Catalase positive. The growth rate of isolated strain was optimized by weighing dry cell and turbidity at 600 nm at different concentrations of dextrose (1%, 5% and 10%). Ten (10) percent dextrose solution showed rapid growth and higher cell mass than 5% and 1% solution respectively. Acidity of the media gradually increased from 0.102% to 2.18% from day 0 to day 7 and pH of the media decreased from 6.8 to 5.5 during the period. This protocol was successful for enriching Acetobacter aceti, which was essential for vinegar production. J. Bangladesh Agril. Univ. 13(2): 299-306, December 2015